2020
DOI: 10.1093/jac/dkaa505
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of inappropriate prescribing in elderly patients of the Swiss HIV Cohort Study reveals gender inequity

Abstract: Background The extent of inappropriate prescribing observed in geriatric medicine has not been thoroughly evaluated in people ageing with HIV. We determined the prevalence of and risk factors for inappropriate prescribing in individuals aged ≥75 years enrolled in the Swiss HIV Cohort Study. Methods Retrospective review of medical records was performed to gain more insights into non-HIV comorbidities. Inappropriate prescribing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…[12][13][14][15] In our sample female participants living with HIV were treated with drug classes usually associated with comorbidities more prevalent in women such as thyroid disorders and, not surprisingly, less with drugs used for ischemic cardiac disease (such as antiplatelet agents) or hypertrophic prostate (such as alpha-blockers). 16 Yet the larger use of cations, antiepileptics and insulin in female participants does not have obvious explanations and requires a thorough correlation with participants' comorbidities. BMI was associated with PP in controls: higher BMI may identify patients with metabolic syndrome and often type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] In our sample female participants living with HIV were treated with drug classes usually associated with comorbidities more prevalent in women such as thyroid disorders and, not surprisingly, less with drugs used for ischemic cardiac disease (such as antiplatelet agents) or hypertrophic prostate (such as alpha-blockers). 16 Yet the larger use of cations, antiepileptics and insulin in female participants does not have obvious explanations and requires a thorough correlation with participants' comorbidities. BMI was associated with PP in controls: higher BMI may identify patients with metabolic syndrome and often type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…While age has constantly been reported as a major risk factor for PP, female gender is not usually recognized as such 12–15 . In our sample female participants living with HIV were treated with drug classes usually associated with comorbidities more prevalent in women such as thyroid disorders and, not surprisingly, less with drugs used for ischemic cardiac disease (such as antiplatelet agents) or hypertrophic prostate (such as alpha‐blockers) 16 . Yet the larger use of cations, anti‐epileptics and insulin in female participants does not have obvious explanations and requires a thorough correlation with participants' comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses have shown that women have more polypharmacy and medication errors. 5,6 The current study did not observe a sex difference in harm from polypharmacy; however, women comprised less than 3% of the study population, thus preventing any definitive conclusion relating to sex differences. Future studies are needed to address this uncertainty and to assess the role of frailty as a potential contributor to the risk of hospitalisation related to polypharmacy.…”
Section: Polypharmacy and Risk Of Admission To Hospital In People Ageing With Hiv: What Is The Contribution Of Drug-drug Interactions?mentioning
confidence: 53%
“…The finding that KPDIs explain only part of the association between polypharmacy and risk of hospitalisation should prompt future studies to investigate the role of prescribing issues other than drug-drug interactions (eg, inappropriate medication, unadjusted dosing), which were found to be common in people ageing with HIV 5 and which might also lead to adverse health outcomes. Previous analyses have shown that women have more polypharmacy and medication errors.…”
Section: Polypharmacy and Risk Of Admission To Hospital In People Ageing With Hiv: What Is The Contribution Of Drug-drug Interactions?mentioning
confidence: 99%
“…There was a total of 36 de nitions of polypharmacy, with studies further divided based on the magnitude of polypharmacy (Table 1); minor polypharmacy (N = 3); major polypharmacy (N = 29); "severe" polypharmacy (N = 2); "excessive" polypharmacy (N = 1); "higher" polypharmacy (N = 1) (Table 2). Major 29 [2], [6], [8], [15], [17][18][19][20][21][22][23][24][25][26][27][28][29], [31][32][33][34][35][36][37][38][39][40] Severe 2 [23] [26] [39] Excessive 1 [11] Higher 1 [39] Duration of Polypharmacy Amongst the included studies, 16% (N = 5) incorporated the duration of treatment to the de nition of polypharmacy, while a signi cant proportion 84% (N = 26) only provided the numerical de nition of polypharmacy with no additional information on its duration. Gimeno-Gracia et al further strati ed drug exposure based on the following duration: greater than 1 day; greater than 90 days; and greater than 180 days [14,36].…”
Section: Resultsmentioning
confidence: 99%